Do consumers pay voluntarily?: the case of online music - Tobias Regner; Javier A. Barria (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
The paper analyses the payment behaviour of customers of the online music label Magnatune. Customers may pay what they want for albums, as long as the payment is within a given price range (5-18). Magnatunes comprehensive pre-purchase access facilitates music discovery and allows an informed buying decision setting it apart from conventional online music stores. On average customers pay 8.20, far more than the minimum of 5 and even higher than the recommended price of 8. We analyse the relationship between artists/labels and customers in online music. We consider social preferences, in particular concerns for reciprocity. The resulting sequential reciprocity equilibrium corresponds to the observed pattern of behaviour. We conclude that Magnatunes open contracts design can encourage people to make voluntary payments and may be a viable business option.
Keywords: 330; Konsumentenverhalten; Musikwirtschaft; Internet; Gerechtigkeit; Sozialpsychologie; Spieltheorie